Robot-Assisted Radical Cystectomy for Pediatric Bladder Rhabdomyosarcoma - Nishio, Hidenori (J Endourol Case Rep, 2020)
Background: The standard treatments for muscle-invasive bladder cancer with no metastasis are total cystectomy and urinary diversion. Although robot-assisted radical cystectomy (RARC) was covered from April 2018 by the Japanese National Health Insurance system, and the number of RARC is increasing, there has been no pediatric case report on RARC in Japan. Case Presentation: We report the case of a 6-year-old Japanese girl who was referred to our hospital with the chief complaint of a vulvar tumor protrusion during defecation. We resected the tumor from her external urethral meatus, and transurethral resection for the residual partial bladder neck tumor was performed for both a definitive diagnosis and as a possible curative therapy. The pathologic diagnosis was an embryonic type of rhabdomyosarcoma. Although she was treated by chemotherapy combined with proton therapy, a residual tumor at the neck and a new lesion at the top of bladder were observed 2 years after initial treatment. Thus, RARC was performed. The surgical specimen was placed in an end-pouch and was then removed through the incised vaginal wall, with cosmetic consideration. A bilateral cutaneous ureterostomy was performed at the sites of the working ports for urinary diversion. In the future, we plan to perform abdominal wall catheterization. Postoperatively, she was treated with adjuvant chemotherapy. There was no recurrence for 19 months. Conclusion: Because she was a child, particularly a girl, the wounds should be small and inconspicuous considering the cosmetic aspect. Although the posterior aspect of the bladder seemed difficult to detach because of the adhesions, it was possible to safely perform RARC.